Anti-church Terror during the October Revolution Through the Prism of the Historiografy - S. LEONOV (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article reviews the historiographical data on the Bolshevik repressions against The Russian Orthodox Church during The October Revolution (1917-1921). It explores the main trends and peculiarities of the historiography, starting from its genesis and up to the present days. It points out that in the Soviet historical literature this subject was actually prohibited; and at best, it was addressed only en passant. Only to the end of the “Perestroika” these subjects was actively discussed, but in the press. The basis for the historiography of the anti-church terror during the October Revolution was laid by the Russian emigrants, ﬁrst of all by A. A. Valentinov and M. Pol’skĳ . Essential knowledge was added by the Western historiography, but until 1990’s it had been also restrained by the lack of sources. In contemporary Russia, many studies have appeared on the wave of unprecedented interest to the history of the Church, which review one or another aspect of repressions against clergy and laity during the October revolution. Nevertheless, several key issues still remains disputable since they have never been properly explored, e.g. the directly goals of the Bolsheviks’ policy toward the Church and factors of anti-Church terror; relation of the terror “from above” (oﬃcial/ government structures) to the one “from below”; attitudes of the majority of the rural and urban populations; numbers of repressed members of clergy and laity, etc. As a whole, the problem of anti-Church terror during the October revolution still remains underexplored.